2001
DOI: 10.1097/00000539-200110000-00052
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Relations Between the Cephalic Vein and the Sensory Branches of the Radial Nerve: How Can Nerve Lesions During Vein Puncture Be Prevented?

Abstract: We attempted to determine the relationship between the cephalic vein and the sensory branch of the radial nerve at the wrist to help prevent lesions of the radial nerve when the cephalic vein is cannulated. We examined the anatomy of 33 postmortem specimens and suggest that puncture of the cephalic vein 12 cm or more proximal to the styloid process can prevent radial nerve lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 5 publications
6
20
0
8
Order By: Relevance
“…1,4,6,11,12 Besides, having the knowledge of the variations of the termination and the course of these veins is quite important for surgeons, radiologists, anesthetists and cosmetic surgeons. 1,4,6,[13][14][15] Consequently, we are of the opinion that it would be of great use to the surgeons, radiologists and anesthetists involved in this region (of the body) to have the knowledge of the variations we have described as to external jugular vein and cephalic vein.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,6,11,12 Besides, having the knowledge of the variations of the termination and the course of these veins is quite important for surgeons, radiologists, anesthetists and cosmetic surgeons. 1,4,6,[13][14][15] Consequently, we are of the opinion that it would be of great use to the surgeons, radiologists and anesthetists involved in this region (of the body) to have the knowledge of the variations we have described as to external jugular vein and cephalic vein.…”
Section: Discussionmentioning
confidence: 99%
“…Unusual drainage of CV into basilic vein, internal jugular vein, subclavian vein and external jugular vein has been reported [5][6][7][8]. Due to constant position and sufficiently large size, CV is frequently used for intravenous drug administration [9]. Studies have shown that percutaneous venous punctures are preferred in CV than subclavian vein [10].…”
Section: Discussionmentioning
confidence: 99%
“…Both Robson et al and Samarakoon et al, indicate that to avoid iatrogenic injury of the SBRN, need to avoid cannulation of the CV in the distal third of the forearm. Vialle et al (2001) concluded that to avoid injury to this nerve, CV puncture must be at least 12 cm above the styloid process of the radius.…”
Section: Anatomical Snuffbox Uses and Clinical Significancementioning
confidence: 99%